Soaring The Diary and Letters of a Denishawn Dancer in the Far East, 1925-1926 (Wesleyan University Press, 1976)
An account of the author's travels during her 15 month tour of the Far East with Ruth St. Denis, Ted Shawn, and the Denishawn Dance Company along with Doris Humphrey, Charles Weidman, and Pauline Lawrence, among others. Contains letters and diary entries. In addition to providing a dance history narrative, this book accounts a vivid description of traveling in the Far East in the mid 1920s. Includes primary source letter, journals, and pictures to bring the history directly to the reader.